Corporate Sociability: Analyzing Motivations for Collaborative Regulation. (May 2014) - Findlay, Mark
The article explores the features and charts the principle theorizing of regulatory sociability from collaboration rather than intervention, whatever the interest-based motivation behind transforming crisis, toward orderliness. A key theme is the role played by corporations in facilitating and benefiting from sociability. A particular explanatory focus on the way in which corporate culture can change from predatory jurisdiction shopping to embracing mutuality of interests in the context of environmental sustainability is employed. The article concludes with a discussion of how, as compulsory discipline increases, it may produce compliance but at costs for regulatory sociability. The alternative regulatory paradigm is one that moves to resolve the antimony between desire (profit) and reason (sustainability) in a manner that relies on and endorses the constituents of collaboration. Collaborative regulation, the article suggests, can arise out of crisis and be justified through desires for orderliness without compulsion. But for collaborative regulation to be sustainable, it must complement certain positive "orderly" aspects within political economy. The analysis determines some observations concerning the shape and shaping of collaborative regulation in an atmosphere of more pluralist knowledge-based (disciplinary) engagement involving trust, comity, and sustainability.